Teknologi Internet of Things untuk Meningkatkan Mobilitas Penyandang Tunanetra Tanpa Batasan Ruang dan Waktu - Ramadhani, Muhammad Tachyul Qulub; Imam Purwanto , Imam Purwanto (Computer Engineering Departement, Universitas Komputer Indonesia, 2025)
This system uses NodeMCU ESP8266 and ESP32 CAM to create a cane for the visually impaired. The HC-SR04 ultrasonic sensor detects objects within a distance of 50 cm and activates a buzzer as a warning. The buzzer will ring if the yellow guidance route is not identified by the TCS3200 color sensor. When the water level hits a certain point, the water sensor sounds the buzzer to warn of flooding. Locations are tracked by the GPS module, and alerts with a link to Google Maps are sent out with the findings. The camera module is used for real-time monitoring through the Blynk platform, allowing users to see the surrounding conditions. This research tests the effectiveness of the tool by measuring the accuracy of GPS signals in various locations and the quality of video from the camera under different conditions. To enhance the effectiveness of the tool, it is recommended to add a DC motor for automatic braking, touch sensors, advanced cameras, and an MP3 module for sound output. The research method includes design and construction as well as data collection from the analysis results during testing. This system is designed to facilitate the travel of visually impaired individuals by providing early warnings about obstacles, going off course, or puddles Keywords - Camera; Color; Distance; Location; Water